Concentration and Distribution of Oligochaeta Worms in the Waters of Kejapanan, Pasuruan, Indonesia Polluted by Mercury Waste using DNA Barcode - Irawati Mei Widiastuti; Moh. Awaludin Adam; Ernawati (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract